2021
DOI: 10.1007/s11412-021-09346-6
|View full text |Cite
|
Sign up to set email alerts
|

Improving learning and writing outcomes: Influence of cognitive and behavioral group awareness tools in wikis

Abstract: Group awareness (GA) tools can facilitate learning processes and outcomes by visualizing different social attributes, such as cognitive and behavioral information about group members. To assist learning and writing in social media, combining various types of awareness information may foster learning processes due to challenges, which are difficult to address by one type of GA information alone. The systematic investigation of GA tool combinations is largely unexplored with GA information often being examined s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…With the popularization of information technology education, there are more and more types of educational technology tools; however, some studies have shown that the integration value of information technology and education is mainly reflected in the container for storing and disseminating information, and learners lack the ability to learn independently [12]. The construction of classroom teaching in the future should reflect the learner-centered constructivist design concept, and the external presentation of knowledge should echo the learner's internal cognitive structure [13,14]. In the past, traditional classroom teaching was mainly conducted by teachers in front of the blackboard, which not only limited the classroom time but also had poor interaction between teachers and students, and students' learning enthusiasm was low, Exploring methods to improve teaching quality through online interactive teaching and making effective eduacational resources play a full role are problems worth thinking about at the moment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the popularization of information technology education, there are more and more types of educational technology tools; however, some studies have shown that the integration value of information technology and education is mainly reflected in the container for storing and disseminating information, and learners lack the ability to learn independently [12]. The construction of classroom teaching in the future should reflect the learner-centered constructivist design concept, and the external presentation of knowledge should echo the learner's internal cognitive structure [13,14]. In the past, traditional classroom teaching was mainly conducted by teachers in front of the blackboard, which not only limited the classroom time but also had poor interaction between teachers and students, and students' learning enthusiasm was low, Exploring methods to improve teaching quality through online interactive teaching and making effective eduacational resources play a full role are problems worth thinking about at the moment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another finding is that there is a positive relationship between adversative conjunctions and integrative perspective arguments. This shows that the more intense the use of adversative conjunctions, the greater the presence of integrative perspective arguments in the students' argumentative essays (Ollesch et al, 2021;Weston-Sementelli et al, 2018).…”
Section: Discussionmentioning
confidence: 86%
“…Using this method, the researchers were able to classify the types of arguments used by the students. The researchers also adapted Crowell's coding scheme to assess the results of the analysis because this scheme can investigate the level of complexity of the students' argumentative essays and also assess the movement of the arguments they use as opposing arguments (Deane et al, 2021;Ollesch et al, 2021).…”
Section: Learning To Write Arguments At Schoolmentioning
confidence: 99%
“…Research on CSCL has investigated different types of GATs. While cognitive group awareness tools visualize different aspects of the knowledge that is available in the group (e.g., Dehler et al, 2011;Engelmann & Hesse, 2011;Ollesch et al, 2021), social group awareness tools provide information about processes and states of group members such as participation (Bachour et al, 2010;Janssen et al, 2011;Ollesch et al, 2021;Strauß & Rummel, 2021b), how much information has been shared (Kimmerle & Cress, 2009) or how the members of a group perceive each other (Phielix et al, 2011). In this chapter, we focus on social group awareness tools.…”
Section: Feed-back On Interaction: How Group Awareness Tools Guide Co...mentioning
confidence: 99%